The Effect of Work Stress and Workload on Turnover Intention at Surya Toserba Jatiwangi - Mahesa Putra; Agung Ramadhan; Muhammad Alwi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine and analyze the effect of job stress and workload on turnover intention among employees of Surya Toserba Jatiwangi. The research method used was a quantitative method with a sample of 93 respondents. The results of the analysis indicate that job stress has a positive and significant influence on turnover intention. In addition, workload also has a positive and significant influence on turnover intention. Simultaneously, job stress and workload influence turnover intention by 48%. Thus, the research hypothesis is accepted, indicating that the higher the level of job stress and workload, the greater the employee turnover intention. The results of this study emphasize the importance of effective management of job stress and workload to reduce employee turnover rates in the company.